2021
DOI: 10.1166/sam.2021.3921
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Mechanical Characterization of Poly(methyl methacrylate) Based Cements for Bone Regeneration

Abstract: This laboratory study set out to characterize Calcium Phosphate (CaP) based bone cements with added Zinc Oxide (ZnO) embedded in Poly (methyl methacrylate) (PMMA). Bone cements with varying percentages of CaP mixed with and without varying percentages of ZnO in PMMA were fabricated by one-step polymerization by reacting equimolar ratios of MMA powder and acrylic resin. Neat-PMMA was used as control throughout the experiment. Fabricated samples were tested for their contact angle measurement, surface roughness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Resin‐based materials, on the other hand, do not possess intrinsic antibacterial properties, and that microorganism can metabolize set resin matrix (Khan et al, 2019; Khan et al, 2018; Sheikh et al, 2021). Previous studies have investigated the antimicrobial function of the resin materials containing fluoride and revealed that while they have substantial antibacterial activity at initially, their release rates do not endure long (Cury et al, 2016; Itota et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resin‐based materials, on the other hand, do not possess intrinsic antibacterial properties, and that microorganism can metabolize set resin matrix (Khan et al, 2019; Khan et al, 2018; Sheikh et al, 2021). Previous studies have investigated the antimicrobial function of the resin materials containing fluoride and revealed that while they have substantial antibacterial activity at initially, their release rates do not endure long (Cury et al, 2016; Itota et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Resin-based materials, on the other hand, do not possess intrinsic antibacterial properties, and that microorganism can metabolize set resin matrix (Khan et al, 2019;Sheikh et al, 2021).…”
Section: Introductionmentioning
confidence: 99%